Processing freshly harvested banagrass to improve fuel qualities: Effects of operating parameters. (October 2017) - Cui, Hong; Turn, Scott; Morgan, Trevor; Li, Dong
Abstract: Mechanical dewatering and leaching were used to process freshly harvested banagrass ( Pennisetum purpureum X Pennisetum glaucum ) and improve fuel properties relevant to thermochemical conversion. A factorial, 2 3 experiment determined the effects of process operating parameters: particle size (1 mm and 80 mm), rinse water temperature (25 °C and 75 °C), and rinse duration (1 min and 3 min). Characterization of the samples from the process included moisture and ash contents of solid samples, potassium (K) and chlorine (Cl) contents of solid and liquid samples, and chemical oxygen demand, total solids, and total suspended solids of liquid samples. These were used to assess the effectiveness of treatment on reducing K and Cl in the processed material, estimate material/energy losses associated with the processing, and identify further treatment requirements and opportunities for material recovery. The effects of particle size, rinse water temperature, and their interaction indicate that processing with low-grade hot water (75 °C) can improve K and Cl removal by over 10% compared to treatment using ambient temperature water for larger particles (80 mm). The former could result in reduced capital and operating costs for size reduction, as well as reduced material losses during processing. Highlights: Particle size and rinse temperature have significant effects on the processing. Low-grade steam or hot water is a substitute for size reduction of feedstock particle. Larger particle sizes resulted in lower "material loss" during the processing.